Mining Irish-American lives : western communities from 1849 to 1920 - Noonan, Alan J. M. (Mining the American West., 2022)
"Mining Irish-American Lives uses previously uncovered sources--emigrant letters, hospital log books, private detective reports, and internment records--to tell the stories of Irish men and women who emigrated to mining towns, investigating their lives through the prism of their own experiences."--